2022
DOI: 10.3389/fnins.2022.1021131
|View full text |Cite
|
Sign up to set email alerts
|

Perivascular spaces as a potential biomarker of Alzheimer’s disease

Abstract: Alzheimer’s disease (AD) is a highly damaging disease that affects one’s cognition and memory and presents an increasing societal and economic burden globally. Considerable research has gone into understanding AD; however, there is still a lack of effective biomarkers that aid in early diagnosis and intervention. The recent discovery of the glymphatic system and associated Perivascular Spaces (PVS) has led to the theory that enlarged PVS (ePVS) may be an indicator of AD progression and act as an early diagnost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 142 publications
0
12
0
Order By: Relevance
“…Previous works have suggested inadequate drainage of CSF‐ISF might contribute to the Aβ accumulation in AD. [ 30,31 ] Hereby, the observations in transgenic AD model mice (Figure 4 and Supplementary Videos 4–6) revealed the interactions between the glymphatic clearance and the pathological factor Aβ. Elevated Aβ is one important aspect of AD pathology recapitulated in the APP/PS1 model.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Previous works have suggested inadequate drainage of CSF‐ISF might contribute to the Aβ accumulation in AD. [ 30,31 ] Hereby, the observations in transgenic AD model mice (Figure 4 and Supplementary Videos 4–6) revealed the interactions between the glymphatic clearance and the pathological factor Aβ. Elevated Aβ is one important aspect of AD pathology recapitulated in the APP/PS1 model.…”
Section: Discussionmentioning
confidence: 74%
“…Remarkably, even once the blood flow was fully recovered (Supplementary Video 6), the tracer appeared to be partially retained, with an uneven, “gurgling” flow near the wall. Therefore, despite increased numbers of pores in AD model mice, the viscous, high Aβ‐content CSF could exceed the drainage capacity of even pore‐enriched vessels, which may lead to CSF retention that could be associated with the perivascular space dilation, a known indicator of AD progression [ 30 ] due to declined glymphatic clearance prior to the formation of amyloid plaques. [ 31 ]…”
Section: Resultsmentioning
confidence: 99%
“…In addition, two studies found an association of MVPVS with tau by employing flortaucipir PET ( Sepehrband et al, 2021 ; Wang et al, 2021 ) or CSF analysis ( Wang et al, 2022 ). It is also noteworthy that it is still under debate whether MVPVS formation is the consequence or driver of vascular protein deposition ( Lynch et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Inclusion of other vascular measures, such as lacunar infarcts, perivascular space enlargement, and microbleeds would have provided additional validity to the VDF. Recent work has reviewed the role of perivascular spaces in AD, 32 and elucidated its contribution to early cognitive decline based on the ADNI data 33 . The methods for automatic quantification of PVS are being developed by different groups, but these methods need to be evaluated for consistency 34–36 .…”
Section: Discussionmentioning
confidence: 99%